Establishment of an Improved Acetyl Chloride-Methanol Method for the Determination of Fatty Acids in Infant Foods for Special Medical Purpose Based on Simulation Experiments - LI Jie, TIAN Qiyan, LIU Yanming, WANG Yanli, LI Haixia, ZHANG Hui, LIANG Xiuqing, LI Fangfang, JU Xiang, WANG Jun, HU Mei (Shipin Kexue, 2024)
An improved acetyl chloride-methanol method was established for the rapid and accurate determination of linoleic acid, α-linolenic acid, docosahexaenoic acid (DHA) and arachidonic acid (ARA) in infant foods for special medicinal purpose with deeply hydrolyzed milk proteins and amino acids. The results showed that the optimal pretreatment conditions were 6 mL of reaction reagent, reaction for 60 minutes, and use of isooctane as extraction solvent. The linear range of linolenic acid and α-linolenic acid were 0.8–8.0 and 0.2–2.0 mg/mL, respectively. The linear ranges of DHA and ARA were 0.02–0.40 mg/mL, and the determination coefficients for all analytes were greater than or equal to 0.999 7. The limits of detection (LOD) and limits of quantitation (LOQ) of the developed method were 2 and 5 mg/100 g, respectively. This method was characterized by good repeatability (relative standard deviation (RSD) ≤ 3.3%), high precision (RSD ≤ 3.8%), good stability (RSD ≤ 2.6%), and high spiked recovery (ranging from 93.1% to 101.7%). Compared with its original version, the developed method could effectively solve the problem of incomplete reaction due to caking, with an at least 100% higher working efficiency.